Desenvolvimento e pré-teste de um questionário de frequência alimentar para graduandos - Carvalho, Fernanda Sanches [UNIFESP] (2010)
Objective The objective of this study was to develop and pretest a self-administered, quantitative food frequency questionnaire for undergraduate students of the health sciences. Methods This is a cross-sectional study with 151 undergraduate students of both genders from the Students' Healthcare Service of the Universidade Federal de São Paulo (UNIFESP), Brazil. The first version of the food frequency questionnaire was based on the foods and preparations listed in the 3-day food records. Tables were used to convert cooking units into grams or milliliters and the foods were ranked according to their percentage contribution to the total calorie intake. The 198 foods responsible for 95% of the energy intake were selected and grouped into 77 food items according to nutritional resemblance. Serving size was classified according to the 50th percentile of the weight distribution corresponding to the cooking units. Serving size was defined as small (S) when £25th percentile; average (A) when equal to the 50th percentile and large (L) when ≥75th percentile. Results The pretest of the first version of the questionnaire resulted in a final version with a list of 89 foods, grouped into 70 food groups. The instructions for filling out the questionnaire were rewritten to get better answers from the students. Conclusion After these changes, the quantitative food frequency questionnaire is ready for the validation and calibration study.